Outcomes of Open Adoption from Care An Australian Contribution to an International Debate - Ward, Harriet (Springer Nature, 2022)
This Open Access book presents unique evidence from the first comprehensive study of the outcomes of open adoption from care in Australia. It contributes to the international debate concerning the advantages and disadvantages of face-to-face post adoption contact with birth families. The chapters assess whether adoption provides a better chance of permanence and more positive outcomes than long-term foster care for abused and neglected children in care who cannot safely return to their birth families. They also explore whether open adoption can avoid some of the detrimental consequences of past policies in which adoption was shrouded in secrecy and children frequently grew up with a conflicted sense of identity. The book will appeal to policy makers, practitioners and students of social policy, social work, the law, psychology and psychiatry. It should also be of interest to adult adoptees and adoptive parents, whose experiences it reflects.